1974
DOI: 10.1530/jrf.0.0390011
|View full text |Cite
|
Sign up to set email alerts
|

The Gonadotrophic Hormone Response of Anoestrous and Cyclic Ewes to Synthetic Luteinizing Hormone-Releasing Hormone

Abstract: Summary. Anoestrous and cyclic ewes were treated with luteinizing hormone-releasing hormone (LH-RH) by intravenous (i.v.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

1975
1975
1986
1986

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 7 publications
2
13
0
Order By: Relevance
“…The releases of LH observed in response to Gn-RH are in agreement with other studies (Foster & Crighton, 1973) and are similar to Gn-RH-evoked releases in anoestrous and spayed ewes (Reeves et al, 1972;White, Hedlund, Rippel, Arnold & Flouret, 1973 ;Radford & Wallace, 1974;Symons, Cunningham & Saba, 1974). The pattern of release of LH was similar on Days 12 and 25 after lambing, but significantly more was released at the later time, indicating a change in pituitary sensitivity to Gn-RH, a change in pituitary content of LH, or increased synthesis.…”
Section: Discussionsupporting
confidence: 89%
“…The releases of LH observed in response to Gn-RH are in agreement with other studies (Foster & Crighton, 1973) and are similar to Gn-RH-evoked releases in anoestrous and spayed ewes (Reeves et al, 1972;White, Hedlund, Rippel, Arnold & Flouret, 1973 ;Radford & Wallace, 1974;Symons, Cunningham & Saba, 1974). The pattern of release of LH was similar on Days 12 and 25 after lambing, but significantly more was released at the later time, indicating a change in pituitary sensitivity to Gn-RH, a change in pituitary content of LH, or increased synthesis.…”
Section: Discussionsupporting
confidence: 89%
“…Similar biphasic responses to infusions of LH-RH have been observed in man (Bremner & Paulsen, 1974) and to a certain extent in the rat , and have been proposed as evidence for the existence of two pools of LH. In the rat, LH levels decline after a few hours of infusion, and a similar termination of responsiveness to infused LH-RH has been observed in the sheep, though a biphasic response was not described (Chakraborty, Adams, Tarnavsky & Reeves, 1974;Symons, Cunningham & Saba, 1974;Shareha, Ward & Birchall, 1976). Such a decrease during the course of the infusions in the present study on the guinea-pig was not observed, possibly because of the relatively short period of infusion.…”
Section: Discussionsupporting
confidence: 75%
“…The ovary during anoestrus contains follicles which appear macroscopically similar to the follicles present during the breeding season (Cole & Miller, 1935;Kammlade, Welch, Nalbandov & Norton, 1952;Mallampati & Casida, 1970;Roche et al 1970). The concen¬ trations of oestradiol (Reeves, Tarnavsky & Chakraborty, 1974;Yuthasastrakosol et al 1975) and progesterone (Symons, Cunningham & Saba, 1974;Yuthasastrakosol et al 1975) measured in peripheral plasma are low during anoestrus. During the breeding season, oestradiol and androstenedione are secreted almost entirely from the follicular compart¬ ment of the ovary ).…”
Section: Discussionmentioning
confidence: 94%